PENGUATAN PENEGAKAN HUKUM HAK KEKAYAAN INTELEKTUAL (Studi Kritis terhadap Peran Pendidikan Kewarganegaraan) - Triyanto, - (Yustisia, 2012)
AbstractThis study discusses the role of Civic/Citizenship Education (CE) in strengthening IPR law enforcement. This study aimed to identify: (1) the effectiveness of IPR law enforcement has done; (2) the constraints; (3) the efforts to overcome obstacles; (4) CE Model of IPR National Team; (5) weakness of the CE model of IPR National Team; (6) efforts to overcome the weaknesses of the CE model of IPR National Team; and (7) the role of CE to strengthen IPR law enforcement. The research used a qualitative method. The samples of the research were gathered by using purposive sampling and snowball sampling techniques. Its data were gathered through library research, in-depth interview, observation, and focus group discussion. They were then analyzed by using interactive (Miles & Huberman, 1984: 23) and bottom up (Creswell, 2008: 244) models of analysis. The results of the research show that: (1) the law enforcement for the IPR has not been effective; (2) The law enforcement for the IPR has encountered some constraints caused by the factors of law enforcement apparatus, community, and holders of the IPR; (3) The efforts to overcome the constraints of IPR law enforcement needs to be done in a systematic approach involving educational approach; (4) CE Model of IPR National Team can be seem in preemptive and preventive actions; (5) the weakness of the CE Model of IPR National Team is the absence of IPR education approach for early childhood; (6) The IPR education program for early childhood can be used to overcome the weakness, with the cooperation of private funding and the use of CSR; (7)  In conclusion, CE can be used as means of IPR education through the implantation of the values of honesty, respect and appreciation of one’s rights (IPR) for early childhood.Keywords:         Improving the Law Enforcement, Intellectual Property Rights, and, Civic/Citizenship Education AbstrakTujuan dari penelitian ini adalah untuk mengetahui peran Pendidikan Kewarganegaraan (PKn) dalam memperkuat penegakan hukum Hak Kekayaan Intelektual (HKI). Penelitian ini menggunakan metode kualitatif. Pengambilan sampel menggunakan metode purposive sampling and snowball sampling. Data dikumpulkan dengan menggunakan metode studi pustaka, wawancara, observasi dan focus group discussion (FGD). Data kemudian dianalisis menggunakan model analisis interaktif dan bottom up. Hasil penelitian menunjukkan bahwa PKn dapat menjadi wahana pendidikan kesadaran HKI melalui internalisasi nilai-nilai yang terkandung dalam PKn dan HKI. Kesimpulannya, PKn dapat digunakan sebagai sarana pendidikan kesadaran HKI melalui penanaman nilai-nilai kejujuran, penghormatan dan penghargaan terhadap hak orang lain sejak usia dini.Kata Kunci: Penegakan Hukum, HKI, PKn